Compostos fenólicos e atividade antioxidante em fermentados alcoólicos de diferentes cultivares de mirtilo - Santos, Roberta Oliveira (2015)
Blueberries are an original fruit from the northern hemisphere, where it is grown and marketed on a large scale, especially in the United States, Canada, France and Germany. In recent years the blueberry has received special attention especially for its beneficial health properties due to the presence of antioxidant compounds. Currently the production grows gradually, however due to low shelf life, it is necessary to study new ways of processing for products that allow the flavor and functional properties of the fruit to be enjoyed even outside of the crop. The blueberry wine making is an alternative to enlarge the beverage industry and offers to the consumer a value-added product as well as a new market for Brazilian blueberry producers. The objective of this study was to produce wines from blueberries cultivated in Brazil, explore their antioxidant properties and investigate the relationship between fruits and blueberry wines. They also analyze the influence of deacidification and chaptalization in the chemical and sensory characteristics of fermented and observe the behavior of antioxidants compounds and color during storage. Among the cultivars, the cultivar Climax, had the highest phenolic composition, however did not show good extraction. Blueberry wines of Darrow and Elliot cultivars showed the highest concentration of anthocyanins and the highest antioxidant capacity. The use of the calcium carbonate on blueberry wines of Aliceblue cultivar promoted an increase in pH, however the chaptalization with corn syrup originated fermented with high amount of residual sugar and consequently little alcohol. Regarding the preferred color the most preferred wines were those whose red tones stood out in relation to yellow tones, indicating a possible preference for young wines. When stored for 150 days, the alcoholic beverage decreased in anthocyanin content, consistent with the reduction in shades of red. However, a possible transformation of these compounds can justify the increased content of phenolic compounds and maintaining the antioxidant capacity in spite of the oscillation during 150 days of storage.